2020
DOI: 10.1186/s13613-020-00732-1
|View full text |Cite
|
Sign up to set email alerts
|

A lactate-targeted resuscitation strategy may be associated with higher mortality in patients with septic shock and normal capillary refill time: a post hoc analysis of the ANDROMEDA-SHOCK study

Abstract: Background: Capillary refill time (CRT) may improve more rapidly than lactate in response to increments in systemic flow. Therefore, it can be assessed more frequently during septic shock (SS) resuscitation. Hyperlactatemia, in contrast, exhibits a slower recovery in SS survivors, probably explained by the delayed resolution of non-hypoperfusion-related sources. Thus, targeting lactate normalization may be associated with impaired outcomes. The ANDROMEDA-SHOCK trial compared CRT-versus lactate-targeted resusci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 39 publications
0
36
0
2
Order By: Relevance
“…14 Importantly, yet another post hoc analysis of the same study demonstrated an association between lactate-based resuscitation and higher mortality if capillary refill time was normal at enrollment. 23 This finding calls into question the current practice of attempting to normalize lactate in patients with sepsis and septic shock, although confirmatory studies are needed. If capillary refill time is chosen as a resuscitation target, it should be performed in a systematic fashion as in the original trial.…”
Section: Resuscitation Targets In Sepsis and The Role Of Fluid Therapymentioning
confidence: 99%
“…14 Importantly, yet another post hoc analysis of the same study demonstrated an association between lactate-based resuscitation and higher mortality if capillary refill time was normal at enrollment. 23 This finding calls into question the current practice of attempting to normalize lactate in patients with sepsis and septic shock, although confirmatory studies are needed. If capillary refill time is chosen as a resuscitation target, it should be performed in a systematic fashion as in the original trial.…”
Section: Resuscitation Targets In Sepsis and The Role Of Fluid Therapymentioning
confidence: 99%
“…lactate-targeted resuscitation in terms of mortality in 424 septic shock patients. Even though it failed to reach statistical significance ( p = 0.06), the CRT-targeted strategy was associated to lower mortality at 28 days, which has been recently confirmed by several post-hoc analyses [ 71 73 ].…”
Section: Monitoringmentioning
confidence: 74%
“…In a Bayesian reanalysis of the trial, there was a beneficial effect of CRT target on 28-day mortality, and in post hoc analysis, among those with normal CRT, those within the lactatetargeted group had higher 28-day mortality (OR: 3.3, 95% CI: 1.5-7.1). 102,103 Patients in the lactate group received more fluid within the first 8 hours (mean difference: þ408 mL, 95% CI: þ110-605 mL, p ¼ 0.01) and had more organ dysfunction at 72 hours (mean SOFA difference: 1.00, 95% CI: 0.02-1.97, p ¼ 0.045).…”
Section: Does Lactate-guided Therapy Cause Over-resuscitation?mentioning
confidence: 99%